Smart and efficient system for the detection of wrong cars parking - A. H. M. Almawgani; Turki Alsuwian; Adam R. H. Alhawari; A. N. Alhuthari; M. A. Alhezabr; M. S. Alharethi; F. H. Alqahtani (Bulletin of Electrical Engineering and Informatics, 2021)
This paper presents a smart and efficient car-parking detection system. The proposed system is comprised of two cameras connected to a mobile system that is devised with Arduino, four DC motors, and PIR sensor placed strategically to monitor parking space, especially within its painted rectangular lines of each parking lot. The mobile monitoring system is automatically responsive to any move they detected as vehicles within the parking space along the rows of parking lots. Once detected, the captured images are processed using the MATLAB software. Any improperly parked cars detected, the cameras will identify their plate numbers, and snap and record it in a database. The designed prototype of the proposed system was tested in five presumed cases. In each case, ten images were processed, thus 50 images were eventually obtained. Out of the 50 images, 48 images corresponded to correct detection whereas the other two images corresponded to wrong detection. Accordingly, the efficiency rate of the proposed smart car-parking monitoring system is 96%. This system offers suitable solution in assisting drivers to park properly within each parking lot and owners of parking area to keep it organized via remote monitoring system.